Pengaruh Diskon, Gratis Ongkos Kirim, Cash on Delivery dan Online Customer Review Terhadap Keputusan Pembelian Online Shopee - Aurellia Augusta Damayanti; Dila Damayanti (Journal of Trends Economics and Accounting Research, 2024)
Online marketing is a strategic process to create good distribution, promotion, pricing and service to consumers using the internet or electronic media. Online marketing focuses on understanding through the use of digital technology and providing information for business marketing. This research purpose to measure the variables of discounts, free shipping, cash on delivery with online customer reviews which own positive or negative effect will consumer purchasing decisions. The research objects used were students in the Special Region of Yogyakarta. The research was carried out quantitatively using an online questionnaire via Google Form on 100 respondents. Fact data analysis used multiple linear regression via SPSS 25 (Statisticall Programe Social Science version twenty five). Based on research results, it is reputable that discounts, free shipping and cash on delivery have positive as well as significanti effect will purchasing decision and online customer reviews do not have significanti effect will purchasing decision. Therefore, it can be determined that increasing discounts, free shipping, cash on delivery with online customer reviews can increase Shopee online purchasing decisions among college students in the Special Region of Yogyakarta.